Oxidative Cyclization of Naphtholic Sulfonamides Mediated by a Chiral Hypervalent Iodine Reagent: Asymmetric Synthesis versus Resolution - Jain, Nikita; Hein, Jason E.; Ciufolini, Marco A. (Synlett, 2019)
A chiral aryl iodide promotes the enantioselective oxidative cyclization of 1-naphtholic sulfonamides, albeit in moderate ee and low yield. The products tend to crystallize as conglomerates. Recrystallization thus increases their ee to > 99% ee. This highly enantioenriched material provides seed crystals for the resolution of the racemate (prepared in high yield by oxidative cyclization with (diacetoxyiodo)benzene in trifluoroacetic acid) by coupled preferential crystallization. This enables the production of significant quantities of highly enantioenriched products, despite the low efficiency of the enantioselective reaction.
Keywords: asymmetric catalysis; coupled preferential crystallization; hypervalent iodine; sulfonamides; resolution